Джентльменское соглашение: [роман] / Чингиз Абдуллаев - Абдуллаев Чингиз Акифович
Экземпляры: ф.2 (2008) / Инвентарный номер: 52305 / Цена: 138.00 / Сис.шифр: 84(2Рос-Рус)6-44 / Авт.знак: А 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос-Рус)6-44